Assessing the Seasonal Dynamics of Nitrate and Sulfate Aerosols at the South Pole Utilizing Stable Isotopes. Issue 14 (22nd July 2019) - Walters, Wendell W.; Michalski, Greg; Böhlke, J. K.; Alexander, Becky; Savarino, Joël; Thiemens, Mark H.
Abstract: Atmospheric nitrate (NO3 − = particulate NO3 − + gas‐phase nitric acid [HNO3 ]) and sulfate (SO4 2− ) are key molecules that play important roles in numerous atmospheric processes. Here, the seasonal cycles of NO3 − and total suspended particulate sulfate (SO4 2− (TSP) ) were evaluated at the South Pole from aerosol samples collected weekly for approximately 10 months (26 January to 25 October) in 2002 and analyzed for their concentration and isotopic compositions. Aerosol NO3 − was largely affected by snowpack emissions in which [NO3 − ] and δ 15 N(NO3 − ) were highest (49.3 ± 21.4 ng/m 3, n = 8) and lowest (−47.0 ± 11.7‰, n = 5), respectively, during periods of sunlight in the interior of Antarctica. The seasonal cycle of Δ 17 O(NO3 − ) reflected tropospheric chemistry year‐round with lower values observed during sunlight periods and higher values observed during dark periods, reflecting shifts from HOx ‐ to O3 ‐dominated oxidation chemistry. SO4 2− (TSP) concentrations were highest during austral summer and fall (86.7 ± 73.7 ng/m 3, n = 18) and are indicated to be derived from dimethyl sulfide (DMS) emissions, as δ 34 S(SO4 2− )(TSP) values (18.5 ± 1.0‰, n = 10) were similar to literature δ 34 S(DMS) values. The seasonal cycle of Δ 17 O(SO4 2− )(TSP) exhibited minima during austral summer (0.9 ± 0.1‰, n = 5) and maxima during austral fall (1.3 ± 0.3‰, n = 6) and austral spring (1.6 ± 0.1‰, n = 5), indicating a shift from HOx ‐ to O3 ‐dominated chemistry in the atmospheric derived SO4 2− component. Overall, the budgets of NO3 − and SO4 2− (TSP) at the South Pole were complex functions of transport, localized chemistry, biological activity, and meteorological conditions, and these results will be important for interpretations of oxyanions in ice core records in the interior of Antarctica. Key Points: The stable isotope compositions of nitrate and sulfate were measured from aerosol samples collected at the South Pole Distinct seasonal cycles were found in both concentration and isotopic compositions resulting from changing contributions of emission sources and oxidation chemistry The budgets of nitrate and sulfate at the South Pole are complex functions of transport, localized chemistry, biological activity, and meteorological conditions